EVALUATING THE EFFECTIVENESS OF PERCUTANEOUS PINNING VS. COLLES’ CAST IN UNSTABLE DISTAL RADIUS FRACTURES: A PROSPECTIVE ANALYSIS OF FUNCTIONAL AND RADIOLOGICAL OUTCOME - BANSAL, PUNEET; SHARMA, ANURAG; SINGH, AMBRISH KUMAR; PRAKASH, GYAN; RANA, ROHIT (International Journal of Current Pharmaceutical Research, 2024)
Objective: Distal radius fractures are among the most prevalent orthopedic emergencies, significantly impacting patient quality of life. This study aimed to compare the effectiveness of closed reduction with percutaneous pinning (CRPP) versus Colles’ cast application (CRCI) in managing unstable distal radius fractures. Methods: A prospective, randomized comparative study was conducted at the Department of Orthopaedic Surgery, Indira Gandhi Medical College and Hospital, involving 80 patients with unstable distal end radius fractures. Participants were systematically randomized into two groups for treatment with CRPP or CRCI. Functional and radiological outcomes were assessed using the Mayo Wrist Score, the Modified Gartland and Werley Scoring System, the Green and O’Brien Score, and Sarmiento’s Modification of lindstrom Criteria. Results: The study found significant improvements in radial length, radial inclination, and volar tilt in the CRPP group compared to the CRCI group. The CRPP group demonstrated superior radiological outcomes and functional recovery metrics, indicating enhanced effectiveness over CRCI in managing unstable distal radius fractures. Conclusion: Closed reduction with percutaneous pinning offers better radiological alignment and functional recovery than Colles’ cast application in the treatment of unstable distal radius fractures, suggesting it as a preferable treatment strategy.